The Effect of Financial Literation on Online Shopping Interest in Millennials - Rini Astuti; Hasrudy Tanjung; Linzzy Pratami Putri (AIBPM Publisher, 2019)
The purpose of this research is to study and analyze financial literacy on online shopping demand in millennials. The support used in this research is associative. The population in this study were all students of the Faculty of Economics and Business, Muhammadiyah University, North Sumatra. Data collection techniques in this study using documentation techniques. Data analysis techniques in this study used the Validity and Reliability Test, and Regression Test. Data processing in this study uses SPSS software version 24.00. The results of the study prove the positive and significant fact of financial literacy on online buying interest.